ICC RULES FOR THE USE OF DOMESTIC AND INTERNATIONAL TRADE TERMS – INCOTERMS 2020 - Fišer-Šobot, Sandra (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The use of trade terms in sales contracts, especially international sales contracts, is customary and very common since it contributes to the acceleration of business transactions increasing, at the same time, their certainty and predictability. ICC Rules for the use of domestic and international trade terms - INCOTERMS 2020 have been in effective use since 1 January 2020. Their goal is to facilitate the conduct of global trade in an easier, more effective and safer manner.In this paper the author analyses development, importance and legal nature of INCOTERMS, with the special reference to its current 2020 revision, having the focus on the seller’s obligation to deliver the goods and risk transfer from the seller to the buyer.
Keywords: contract for the international sale of goods; trade terms; INCOTERMS; delivery of the goods; transfer of risk